Educational Counseling on Bullying Prevention in the School Environment - Hernita, Hernita; Sari, Dwi Amalia; Bukhari, Bukhari; Fatna, Nesa; Sari, Novita; Rabi’al, Jihan (Multidisiplin Pengabdian Kepada Masyarakat, 2026)
Bullying is an aggressive behavior that is carried out intentionally and repeatedly by individuals or groups who possess greater power against those who are weaker, whether physically, verbally, socially, or through digital media. This phenomenon has become a serious problem in Indonesia, particularly within the school environment, with a relatively high prevalence in the Southeast Asian region. Data from the Indonesian Child Protection Commission (KPAI) and the Office of Women’s Empowerment and Child Protection indicate that bullying cases most frequently occur at the elementary school level. The high incidence of bullying among school-aged children is closely related to ongoing cognitive, physical, mental, and social development, which makes children vulnerable to moral and social problems. Bullying behavior is influenced by internal factors such as age, gender, and personality characteristics, as well as external factors including family, environmental conditions, and peer influence. The impacts of bullying are extensive for both victims and perpetrators, ranging from psychological disorders and decreased academic achievement to an increased risk of antisocial behavior in the future. Therefore, bullying prevention requires the involvement of multiple stakeholders through education, strict school policies, the strengthening of the roles of teachers and counselors, and the utilization of technology. These integrated efforts are expected to create a safe, inclusive educational environment that supports optimal child development.